Exploratory interviews with Australian clinical research staff on how they communicate with participants - Wells, Gudrun; Bowden, Janelle; Colyer, Duncan; Kay, Eleonora; Lukeman, Sarah; Newett, Lyndsay; Eckstein, Lisa (BMC medical research methodology, 2024)
Background The connection between participants and their research team can affect how safe, informed, and respected a participant feels, and their willingness to complete a research project. Communication between researchers and participants is key to developing this connection, but there is little published work evaluating how communication during clinical research is conducted. Purpose This paper explores what communications happen (and how) with research participants in Australia post consenting to participate in clinical research. It provides reflections from Australians working in clinical research about their current strategies, or those they would like to use, to communicate with research participants. Methods This exploratory, qualitative descriptive study reports findings associated with twenty semi-structured interviews that were undertaken with people who work in clinical research in Australia (such as staff in participant facing, site management, or sponsor representative roles). These interviews were conducted and analysed inductively using thematic analysis. Findings Research staff reported using a range of communication strategies which varied in implementation, uptake, and suitability between clinical research studies and sites. Four major themes were identified in the interviews: [ 1 ] staff use innovative pragmatism to communicate; [ 2 ] staff tailor the communication strategies to fit the participants’ context; [ 3 ] the site, its systems, and staff training all impact communication; [ 4 ] successful communication requires collaboration between stakeholders. Conclusion There are a variety of communication strategies, methods and activities research staff currently employ with trial participants, which vary in purpose, method, resources required, and suitability between studies and sites. Thorough consideration of the participants’ contexts and the capacity of research sites is crucial for the design of studies which allow for effective communication between the research team and participants. The authors encourage those developing clinical research projects to involve site staff and consumer representatives early in planning for communication with participants.